Fashion Style Mahasiswa pada Era Postmodernitas (Sebuah Telaah Fakta Sosial dalam Tinjauan Sosiologis) - Masrizal, Masrizal; Anggreini, Sevtia Husna; Khairulyadi, Khairulyadi; Yusuf, Bukhari; Fakhrurrazi, Fakhrurrazi (Jurnal Empirika, 2024)
This study aims to describe the fashion style among Syiah Kuala University students who follow the fashion trend of the postmodern era with the perspective of Modernization Theory as described by Anthony Giddens. The study uses a qualitative research method with phenomenology. Data was collected through non-participant observation, interviews with students as informants, and documentation. Data analysis used the analysis of lifestyle disorientation theory in the Postmodernism era. The study results show that Syiah Kuala University students have participated in the developing fashion trend, reflected in the fashion style in clothing and goods consumed as a reflection of self-appearance. The supporting factors for students to display this fashion style are increasingly sophisticated technology, modern cafes that continue to increase in the city of Banda Aceh, and social conformity